The Influence of The Intensity of Parent-Child Interaction on The Tendency of Passive Behavior in Children - Ghifari, Muhammad Iqbal; Maulana, Al Ready Zidan; Fikri, Aqil Izzul (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2023)
The interaction or communication that is want to be achieved is effective communication. Effective communication can create a family environment that is understanding, pleasant, influences attitudes, better relationships and such actions are also expected to maintain effective communication between parents and children, so that in the end it will create a harmonious relationship. This research was conducted to determine the effect of the intensity of communication between parents and children on passive behavior in students from the Faculty of Communication and Multimedia, Universitas Mercu Buana Yogyakarta. Quantitative approach was used to conduct this research. Questionnaire was used to collect data. The results show that the intensity of communication has a big effect on the tendency of passive behavior in children. Where the magnitude of the influence is equal to 55.3%, and other factors as much as 44.7% are influenced by other factors that have not been studied.